Queers and bewitched: Temporada de huracanes of Fernanda Melchor (Anclajes, 2019)
In this essay the character of la Bruja (The Witch) in Fernanda Melchor’s novel Temporada de huracanes is analysed, highlighting the characteristics that resemble the literary and historical archetype: flight, transformation into animals, pacts and copulation with the Devil, elaboration and prescription of herbal remedies, dances and sexual diversity practices. From the theories of Silvia Federici, Paul B. Preciado and Sayak Valencia Triana are analyzed the queer sexualities and the current gore violence of some mexicans towns, that Melchor recreates in her novel of queer-crip realism.
Keywords: Fernanda Melchor; Veracruz; Witch; Sycorax; queer; cripple; gore